2015
DOI: 10.1088/0067-0049/220/2/27
|View full text |Cite
|
Sign up to set email alerts
|

INTERSTELLAR NEUTRAL HELIUM IN THE HELIOSPHERE FROM IBEX OBSERVATIONS. II. THE WARSAW TEST PARTICLE MODEL (WTPM)

Abstract: We have developed a refined and optimized version of the Warsaw Test Particle Model of interstellar neutral gas in the heliosphere, specially tailored for analysis of IBEX-Lo observations. The former version of the model was used in the analysis of neutral He observed by IBEX that resulted in an unexpected conclusion that the interstellar neutral He flow vector was different than previously thought and that a new population of neutral He, dubbed the Warm Breeze, exists in the heliosphere. It was also used in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 47 publications
0
65
0
Order By: Relevance
“…This probability assumes that the ionization rate is constant at a given location and falls off with the inverse square of the heliocentric radius, which is appropriate for photoionization and charge-exchange losses on average. Sokół et al (2015b) describe many details that are similar to our model's implementation, including the formulation of Kepler hyperbolic trajectories and the challenges that this type of modeling must address.…”
Section: Integrated Instrument Response Model Using Analytic Trajectomentioning
confidence: 99%
See 2 more Smart Citations
“…This probability assumes that the ionization rate is constant at a given location and falls off with the inverse square of the heliocentric radius, which is appropriate for photoionization and charge-exchange losses on average. Sokół et al (2015b) describe many details that are similar to our model's implementation, including the formulation of Kepler hyperbolic trajectories and the challenges that this type of modeling must address.…”
Section: Integrated Instrument Response Model Using Analytic Trajectomentioning
confidence: 99%
“…These details are important because the model is not restricted in spin-axis to orientations within the ecliptic or to exact Sun-pointing, and the frame of reference is precisely that of the sensor. (See Sokół et al 2015b for the effect of pointing variation on the observed He rate distributions as a function of the spin-phase and observer longitude.) We have performed numerous validation exercises, several of which we detail here.…”
Section: Observational Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Kubiak et al (2016) analyzed the IBEX-Lo observations with E-step 2 during the early ISN observation seasons 2010-2014 (from mid-November to mid-January of each of those years) and unlike us, assumed that the entire observed signal is due to helium atoms. Using the Warsaw Test Particle model (Sokół et al 2015), they simulated a superposition of neutral He fluxes at Earthʼs orbit originating from two Maxwell-Boltzmann populations of He atoms in the outer heliosheath. They derived the flow parameters of the Warm Breeze through the parameter-fitting method by Swaczyna et al (2015).…”
Section: 7 Ismmentioning
confidence: 99%
“…Beyond this distance, the parameters of these two populations were assumed invariable with time and homogeneous in space. With this, Kubiak et al (2016) fitted the inflow direction and speed, temperature, and density of the Warm Breeze using the nWTPM simulation model (Sokół et al 2015) and data analysis method from Swaczyna et al (2015).…”
Section: Introductionmentioning
confidence: 99%